JURIDIS ANALYSIS OF CONFLICT COMPETENCY OF BUSINESS DISPUTE SETTLEMENT THROUGH ARBITRATION AND GENERAL JUSTICE IN STOCK OWNERSHIP - Edi Prayitno; Martin Roestamy (Magister Hukum Sekolah Pascasarjana Unida, 2017)
This Thesis was written based on the result of legal research that analyzes conflict of business dispute resolution between arbitration and litigation in accordance with the applicable regulation and court decisions which have acquired permanent legal force. The method used in this legal research is normative legal methods. The study of literature as a basis of the research and according to Law Number 30 Years 1999 about Arbitration and Alternative Dispute Resolution, in Article 3 and Article 11 of the Law have expressively stated that District Court does not have the authority to adjudicate disputes between the parties that bound by the arbitration agreement. The result of this legal research is that arbitration clause as stated in business investment agreement that should be absolute competencies to resolve the dispute, but the Decision of District Court Judges which have been strengthened by Supreme Court of Indonesia expressively stated that the court has the authority to check and adjudicate the dispute even it has arbitration clause or arbitration agreement with the reason that the dispute is a tort and there are another parties beside the party who sign the Investment Agreement, in the suit. The court attitude that adjudicate the dispute with arbitration clause lead to conflict of competency and never ending adjudication process of business dispute. From the actual case that researcher has been analyzes, researcher suggest that Supreme Court of Indonesia as the highest judicial body must respect arbitration body by rejecting all of the civil cases that have arbitration clause on its agreement. Law Number 48 Years 2009 about Judicial Power stated that non-litigation dispute resolution is conducted through arbitration or alternative dispute resolution. Based on pacta sun servanda and choice of forum principles on the agreement binding to the parties and must be obeyed by the parties.KeyWord : : Arbitration Clause, Pacta Sun Servanda Principle, Business.